A Facile Synthesis of Dihydropyrimidine-Testosterone-Succinate - Figueroa-Valverde, Lauro; Diaz-Cedillo, Francisco; Garcia-Cervera, Elodia (Asian Journal of Chemistry, 2011)
In this study a new dihydropyrimidine-testosterone-succinate derivative was synthesized. The route involved the preparation of a dihydropyrimidine-testosterone derivative using the threecomponent system (testosterone, benzaldehyde and thiourea) in the presence of hydrochloric acid, followed by esterification of the dihydropyrimidine-testosterone derivative with succinic acid to form a dihydropyrimidine-testosterone-succinate derivative.